INTENSIVE THRESHING MECHANISM IMPROVEMENT - Gennady A. Kuzin; Leonid M. Groshev; Igor A. Khozyayev (Advanced Engineering Research, 2012)
It is shown that the intensive threshing mechanism, containing the drum with smooth rasp bars an d the concave with a convex inlet and canting bars with flanges (_/ - shaped bars) without rods throughout the remaining exte nsion, may become more effective with fuller allowance for mechanical - and - physical properties of the threshed m aterial. The changeabi lity of the classical space geometry between rasp bars under the resistance reduction of the concave is proved. The laboratory tests and test - use of the intensive threshing mechanism are resulted.